Food expenditures of Czechs' households and Engel's law - P. Syrovátka (Agricultural Economics (AGRICECON), 2003)
The paper analyses the pay system in a particular enterprise in the Czech Republic and proposes a change in this system. The establishment of two scales based on pay classes per month is proposed: one scale that allows for overlaps of pay classes but does not allow for overruns into other categories, and another scale that allows for no overlaps at all.